2011
DOI: 10.1371/journal.pone.0017274
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of the Desert Locust Central Nervous System: Production and Annotation of a Schistocerca gregaria EST Database

Abstract: BackgroundThe desert locust (Schistocerca gregaria) displays a fascinating type of phenotypic plasticity, designated as ‘phase polyphenism’. Depending on environmental conditions, one genome can be translated into two highly divergent phenotypes, termed the solitarious and gregarious (swarming) phase. Although many of the underlying molecular events remain elusive, the central nervous system (CNS) is expected to play a crucial role in the phase transition process. Locusts have also proven to be interesting mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 223 publications
(251 reference statements)
4
101
0
1
Order By: Relevance
“…We identified a 1,392-bp contig of the for gene orthologue (36) in an S. gregaria CNS GenBank Expressed Sequence Tags (EST) database (13) and used it as a template to generate a 271-bp dsRNA construct (SI Appendix, Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified a 1,392-bp contig of the for gene orthologue (36) in an S. gregaria CNS GenBank Expressed Sequence Tags (EST) database (13) and used it as a template to generate a 271-bp dsRNA construct (SI Appendix, Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…That newly acquired and fully consolidated gregarious behaviors are mechanistically distinct also tallies with the finding that 5-HT is elevated only transiently, during the first few hours of crowding (16), and therefore cannot maintain gregariousness in the longer term. Activation of PKA may thus provide the link between a transient 5-HT signal and a later phase of consolidation that entails changes in gene expression (11,13). However, previous studies have demonstrated that, after as much as 24 h of crowding, the newly acquired gregarious state is rapidly lost upon reisolation (51), suggesting a prolonged period after 5-HT levels have decreased during which gregarization is still realized through labile modifications of neuronal properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was suggested that CRF/DH may regulate satiety and signal the end of the meal in locusts (Gäde and Goldsworthy 2003). Starting from partial precursor sequences found in the S. gregaria EST database (Badisco et al 2011), two full precursor sequences were obtained, each encoding the CRF-like DH as well as one of both long "ovary maturating parsin" (OMP) isoforms (Van Wielendaele et al 2012). The encoded DH proved to be identical to the CRF/DH of L. migratoria (Kay et al 1991;Lehmberg et al 1991).…”
Section: Crf-related Diuretic Hormonementioning
confidence: 99%